2003
DOI: 10.1002/hed.10285
|View full text |Cite
|
Sign up to set email alerts
|

Sinonasal adenocarcinoma: Immunohistochemical marking and expression of oncoproteins

Abstract: Strong HER-2/neu staining in some cases suggests this oncogene may be involved in the genesis of SNA. Immunohistochemical staining with cytokeratin 7 may be potentially useful in differentiating primary from metastatic disease in sinonasal adenocarcinomas of the intestinal subtype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 23 publications
2
15
0
1
Order By: Relevance
“…Notably, in larger studies, SNAIT and CRAIT showed similar histologic subtypes such as mucinous adenocarcinoma, signet ring carcinoma, and globlet cell carcinoma [2,5,10]. Although no principal differences between SNAIT and CRAIT exist, both tumors of our case showed varying differences of tubular differentiation, proliferation index, and the percentage of chromogranin and CK7-positive cells as previously reported [8,11]. Similar rates of positivity were observed for CDX2 and CK20 [3].…”
Section: Discussionsupporting
confidence: 87%
“…Notably, in larger studies, SNAIT and CRAIT showed similar histologic subtypes such as mucinous adenocarcinoma, signet ring carcinoma, and globlet cell carcinoma [2,5,10]. Although no principal differences between SNAIT and CRAIT exist, both tumors of our case showed varying differences of tubular differentiation, proliferation index, and the percentage of chromogranin and CK7-positive cells as previously reported [8,11]. Similar rates of positivity were observed for CDX2 and CK20 [3].…”
Section: Discussionsupporting
confidence: 87%
“…The most plausible hypothesis is an origin from a transformed duct epithelium [12][13][14][15][16][17]. Transformation of the non-neoplastic respiratory epithelium of the sinonasal tract to an intestinal phenotype, adjacent to adenocarcinoma, has been reported [7,[18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…23,26,27 In addition to mutations, p53 overexpression has been studied; the results obtained indicate that p53 accumulation is a common feature in adenocarcinoma, with immunopositivity ranging between 20 and 80%. 24,27,37 Overexpression of p53 in epithelial cells of ethmoidal mucosa was studied in biopsy samples from 60 woodworkers with a minimum of 10 years of occupational exposure to wood dust and no malignancy, in comparison to 50 nonexposed controls who underwent functional or esthetic nasal surgery, as well as in 15 cases of intestinal type adenocarcinoma. 38 The percentage of cells positive for p53 was significantly higher in wood-dust-exposed subjects in metaplastic epithelium (28.6 versus 7.9%; p < 0.001), in ciliated epithelium (11.7 versus 2.1%; p < 0.001) and in seromucous Cancer Genetics glands of the nasal stroma (12.5 versus 1.0%; p < 0.001).…”
Section: Discussionmentioning
confidence: 99%